Demand For Strategic Food in Rural Indonesia: Applying The Linear Approximation Of The Almost Ideal Demand System - Muhammad Ridwan; Ana Arifatus Sa'diyah; Ninin Khoirunnisa' (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
The urgency of studying strategic food demand in rural households serves as a basis for recommending the formulation of effective and sustainable strategic food policies. This study aims to examine the proportion of rural household expenditure on strategic food, identify the factors influencing rural household consumption of strategic food, and analyze income and price elasticity using the Marshallian approach. The research utilized 2023 Susenas data, which was then analyzed using the LA-AIDS model. The findings indicate that rice is the most preferred commodity among rural households and has a complementary relationship with other strategic commodities. Meanwhile, ruminant meat (beef, goat, and lamb) remains a luxury item for rural households. Government efforts are needed to encourage household consumption of alternative protein sources other than ruminant meat such as chicken, eggs and fish which are relatively affordable.